2021
DOI: 10.1177/1073274820988519
|View full text |Cite
|
Sign up to set email alerts
|

DNA Methylation Based Molecular Subtypes Predict Prognosis in Breast Cancer Patients

Abstract: Background: Epigenetic changes are tightly linked to tumorigenesis development and malignant transformation’ However, DNA methylation occurs earlier and is constant during tumorigenesis. It plays an important role in controlling gene expression in cancer cells. Methods: In this study, we determining the prognostic value of molecular subtypes based on DNA methylation status in breast cancer samples obtained from The Cancer Genome Atlas database (TCGA). Results: Seven clusters and 204 corresponding promoter gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Previous evidence suggests that SLC5A8 alleviates disease progression by regulating the Wnt signaling pathway [16], which requires further exploration in patients with thyroid cancer. Moreover, DNA methylation biomarkers have been reported to accurately predict the prognosis of patients with malignant cancers such as colon [29], breast [30], and pancreatic cancers [31]. Our COX multivariate analysis showed that SLC5A8 methylation is one of the risk factors affecting the prognosis of thyroid cancer.…”
Section: Discussionmentioning
confidence: 66%
“…Previous evidence suggests that SLC5A8 alleviates disease progression by regulating the Wnt signaling pathway [16], which requires further exploration in patients with thyroid cancer. Moreover, DNA methylation biomarkers have been reported to accurately predict the prognosis of patients with malignant cancers such as colon [29], breast [30], and pancreatic cancers [31]. Our COX multivariate analysis showed that SLC5A8 methylation is one of the risk factors affecting the prognosis of thyroid cancer.…”
Section: Discussionmentioning
confidence: 66%
“…Based on selected CpGs in the prior stage, eight studies performed additional feature selection, using methods including LASSO (38, 45, 55, 57, 69, 78, 80), stepwise selection (38, 39), and the Akaike information criterion (64, 77), to further refine the number of CpGs. In contrast, four studies (23, 33, 34)(47) directly trained classification models with clusters as labels using Bayesian networks or random forest, while 17 studies constructed prognostic models (37-39, 45, 46, 53-57, 64, 69, 70, 75, 77, 78, 80). Lastly, models developed in the previous stage were mostly internally validated by split-sample validation, albeit four studies validated the model externally in an independent dataset (33, 50, 57, 78).…”
Section: Resultsmentioning
confidence: 99%
“…Among the 39 studies that adopted clustering-based workflows (5, 18-23, 29, 32-35, 37-39, 43, 45-47, 50, 53-57, 61, 62, 64, 69, 70, 75, 77-80, 83, 84, 87, 88), most started with a preliminary screening of CpG sites (Figure 4.1). The most frequently used pre-selection approach was selecting CpG sites that were significantly associated with prognosis by first performing univariable Cox regression analysis, and then performing multivariable Cox analysis with adjustment for clinical variables.…”
Section: Resultsmentioning
confidence: 99%
“…DNA methylation plays an important role in the progression and prognosis of breast cancer patients. Also, it has an important regulatory role in gene expression in cancer cells (Wu et al, 2021; Zhang et al, 2022). Previously, the downregulation of SVIP in some cancers, such as head and neck tumors, was shown to be associated with hypermethylation of SVIP promoter CpG island (Llinàs-Arias et al, 2019).…”
Section: Discussionmentioning
confidence: 99%